Empowerment in practice : from analysis to implementation - Alsop, Ruth.; Bertelsen, Mette Frost, 1975-; Holland, Jeremy, 1966- (Washington, DC : World Bank, 2006)
This document offers an excellent explanation of the concept of empowerment and develops a very useful framework for disentangling and clarifying the concept. It is both practical and well justified on the basis of the literature. The approach and survey instruments developed to measure empowerment are innovative and very useful. Developing an approach to empirically measure empowerment, and to track empowerment indicators over time in a way that is operationally feasible and consistent with World Bank standards is certainly an outstanding achievement.' --Reginer Birner, Senior Research Fellow, International Food Policy Research Institute, Washington, D.C.
Includes bibliographical references (p. 341-352) and index.
lje 06/02/14
Book
Keywords: Community development; Social planning; Economic development -- Citizen participation